Jesus (pbuh) as “son of God”: a biblical study based on the Jewish scriptures and the gospel of matthew. - Rashid, Ungaran (IIUM Press, International Islamic University Malaysia, 2019)
This article aims to study the phrase “Son of God” that is a common term in the Bible, both in the Jewish Scriptures and the New Testament. The author focuses on the concept of „son of God‟ and other similar terminologies in the Hebrew and Greek languages as transpired in the Bible. The research employs the biblical approach of qualitative methodology in which comparative and textual analysis is applied in some versions of the Bible. The study reveals that the term is used to refer to different things: the nation of Israel, the King of Israel, Prophet Adam a.s. or humankind in general, the Messiah (al-Masīḥ), and also Jesus. Nevertheless, when the term is used to refer to Jesus, there is much confusion and misunderstanding among Christians.